2014
DOI: 10.1002/dneu.22182
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of hypoxia on catecholaminergic locus coeruleus and hypocretin/orexin neurons in chick embryos

Abstract: Terrestrial vertebrate embryos face a risk of low oxygen availability (hypoxia) that is especially great during their transition to air-breathing. To better understand how fetal brains respond to hypoxia, we examined the effects of low oxygen availability on brain activity in late-stage chick embryos (day 18 out of a 21-day incubation period). Using cFos protein expression as a marker for neuronal activity, we focused on two specific, immunohistochemically identified cell groups known to play an important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…To confirm that the optimized CUBIC-clearing and immunostaining protocol provides comparable results to standard histology and immunohistochemistry, we compared our results with those of Godden et al (2014), Landry et al (2014Landry et al ( , 2016 and Chan et al (2016). The stained cells obtained with our optimized protocol showed identical spatial distributions to those obtained in these previous studies at both E16 ( Fig.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…To confirm that the optimized CUBIC-clearing and immunostaining protocol provides comparable results to standard histology and immunohistochemistry, we compared our results with those of Godden et al (2014), Landry et al (2014Landry et al ( , 2016 and Chan et al (2016). The stained cells obtained with our optimized protocol showed identical spatial distributions to those obtained in these previous studies at both E16 ( Fig.…”
Section: Resultsmentioning
confidence: 67%
“…These staining combinations were previously used by Landry et al (2014Landry et al ( , 2016 and Chan et al (2016) in chicken embryos and post-hatched chicks. Light-sheet microscopy of the CUBIC-cleared brains produced images with sufficient resolution to clearly recognize single labelled cells in the hypothalamus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The intensity of cFos staining and the overall morphology of serotonergic and catecholaminergic neurons did not differ among the hypoxic and normoxic groups (Fig. in Landry et al, ). Normal instantaneous heart rate changes have been recorded in E18–19 chick embryos (10% O 2 for 2 h, returned to normoxia; Khandoker et al, ), suggesting the proper functioning of brain circuitry.…”
Section: Discussionmentioning
confidence: 86%
“…At younger ages, more severe hypoxia than used here leads to brain apoptosis, detectable after 6 h of normoxic recovery (Pozo Devoto et al, ). The modest (15% O 2 ) and medium hypoxia (10% O 2 ) are known to be nonlethal at E18 for the exposure times used here (Ferner and Mortola, ; Mortola JP, personal communication; Landry et al, ). We also did not see any of the morphological changes previously described in apoptotic serotonergic neurons (Rahim et al, ), nor any differences in the shape or size of cell nuclei (revealed by cFos and DAPI staining) between control and hypoxic embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation